Answer:
To multiply the expressions (3x + 2y + 1) and (2x - 3y - 5) vertically, we will use the distributive property and multiply each term from the first expression with each term from the second expression.
Starting with the first term in the first expression, which is 3x, we multiply it with each term in the second expression:
(3x) * (2x) = 6x^2
(3x) * (-3y) = -9xy
(3x) * (-5) = -15x
Next, we move to the second term in the first expression, which is 2y:
(2y) * (2x) = 4xy
(2y) * (-3y) = -6y^2
(2y) * (-5) = -10y
Finally, we multiply the last term in the first expression, which is 1, with each term in the second expression:
(1) * (2x) = 2x
(1) * (-3y) = -3y
(1) * (-5) = -5
Now, let's add up all the results:
6x^2 - 9xy - 15x + 4xy - 6y^2 - 10y + 2x - 3y - 5
Simplifying this expression further, we have:
6x^2 - 5x - 6y^2 - 7xy - 13y - 5
Answer:
To multiply the expressions (3x+2y+1) and (2x-3y-5) vertically, you can use the distributive property and follow these steps:
1. Start by multiplying the first term in the first expression, 3x, by each term in the second expression:
- (3x) * (2x) = 6x^2
- (3x) * (-3y) = -9xy
- (3x) * (-5) = -15x
2. Move on to the second term in the first expression, 2y:
- (2y) * (2x) = 4xy
- (2y) * (-3y) = -6y^2
- (2y) * (-5) = -10y
3. Finally, multiply the last term in the first expression, 1, by each term in the second expression:
- (1) * (2x) = 2x
- (1) * (-3y) = -3y
- (1) * (-5) = -5
Now, let's combine the like terms:
6x^2 + (-9xy) + (-15x) + 4xy + (-6y^2) + (-10y) + 2x + (-3y) + (-5)
Simplifying this expression further, we have:
6x^2 - 5x - 9xy + 4xy - 6y^2 - 10y + 2x - 3y - 5
Therefore, the result of multiplying (3x+2y+1) and (2x-3y-5) vertically is 6x^2 - 5x - 9xy + 4xy - 6y^2 - 10y + 2x - 3y - 5.
Step-by-step explanation:
Answer:
The interest he earns in one year is $3000
Step-by-step explanation:
We are given
Alex has $30,000 in his savings account that earns 10% annually
so,
P=30000
r=10%
t=1 years
now, we can find interest
now, we can plug values
now, we can simplify it
So,
The interest he earns in one year is $3000
Answer:
The per capita GDP is 30.925.
Step-by-step explanation:
Since,
Here,
The real G.D.P. = $123.7 billion = $ 123700 million
( 1 Billion = 1000 Million ),
Also, Population = 4 million,
By Substituting the values in the above formula,
Which relation is a function?
(Look at the photo)
Option D didn’t fit in the photo, so here’s it typed out.
x | y
10 15
20 25
8 30
20 35
Answer:
Step-by-step explanation:
Options B, C and D have repeat x-values with different y-values.
The relationship is many-to-one.
If graphed, those point appear on a vertical line.
Option A has one-to-one relation, so is the only functional relationship
Answer:
A is a function.
Step-by-step explanation:
All the others are one-to-many relations.
For example in B, 3 maps to 10 and also maps to 30 ( one - to - many).
A function is a one-to-one or many-to-one mapping.
47, 45, 40, 32, 21, , , , ,
Answer:
7 -10 -30 -53
Step-by-step explanation:
47-2 = 45
45-5 = 40 (2+3=5)
40-8 = 32 (5+3=8)
32-11 = 21(8+3=11).........
21-14 = 7
7-17 = -10
-10 -20 = -30
-30-23 = -53